EVALUASI KINERJA SILIKON DAN PEROVSKITE SEBAGAI BAHAN SEMIKONDUKTOR DALAM TEKNOLOGI SEL SURYA FOTOVOLTAIK - Lihawa, Norman; Ahmad, Agil; ilham, Jumiati; Hidayat, Ikhsan (Journal Of Renewable Energy Engineering, 2025)
This study examines the performance comparison of silicon and perovskite as semiconductor materials in photovoltaic solar cell technology. Silicon is known for its long-term stability, consistent power conversion efficiency, and well-established manufacturing infrastructure. However, its high-temperature, energy-intensive production process raises concerns about cost and environmental impact. In contrast, perovskite offers high power conversion efficiency, tunable material structure, and low-temperature fabrication, but faces major challenges in environmental stability and lead-related toxicity. A literature-based approach was applied, analyzing experimental and simulation data to evaluate key parameters such as energy bandgap, efficiency, carrier mobility, and thermal durability. The analysis indicates that combining both materials in tandem configurations presents a promising strategy for developing more efficient, flexible, and environmentally friendly photovoltaic systems